Analisis Kebijakan Penenggelaman Kapal sebagai Kebijakan Strategis Pemberantasan Illegal, Unreported, and Unregulated (IUU) Fishing di Indonesia Tahun 2014-2017 - Munawar, Musthafa Hadi; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
IUU (illegal, unreported, and unregulated) fishing is addressed as a crime that has caused many losses for Indonesia. To deter the IUU fishing problem, Indonesia has initiated a vessel-sinking policy as a strategic policy. The mentioned problems in this research are why Indonesia implemented the vessel-sinking policy as a strategic policy to deter IUU fishing. In answering the research problem, researcher used the paradigm of constructivism, the concept of identity, and the concept of maritime power as an analytical tool. This research was conducted using qualitative methods with explanative research types through literature study techniques. The vessel-sinking policy as a strategic policy implemented by Indonesia is the result of the act of identity-acquiring as a maritime power carried out by Indonesia. As a country that has maritime superiority, Indonesia has an interest in maintaining its maritime territory from acts of fishing that harm Indonesia. The vessel-sinking policy as a strategic policy is an action prompted by the interests of Indonesia to maintain its maritime superiority